Academic Procrastination and Parenting Styles in Psychology Students - Loa, Reny Iriani (Faculty of Psychology, Universitas Surabaya, 2012)
The aim of this study is to test the correlation between academic procrastination and parenting styles (authoritarian, authoritative, and permissive). Subjects were all psychology students taking their final research paper on the 2011/2012 first semester, therefore the subjects (N=157)were from the 2004-2008 term students. Data collection was obtained from surveys, consisting of the Pure Procrastination Scale (PPS), EVID 2, and Parental Authority Questionnaire (PAQ). The non-parametric data was analysed with the Spearman correlation technique through the SPSS 16.0 program for Windows. Results show no correlation between academic procrastination and authoritarian parenting style, and also no correlation between academic procrastination and the permissive parenting style. The only positive correlation exists between academic procrastination and the authoritative parenting style. Another finding of this study was the negative correlation between parenting styles and need for achievement. Penelitian ini bertujuan untuk menguji hubungan antara prokrastinasi akademik dan pola asuh orang tua (otoriter, otoritatif, dan permisif). Subjek penelitian ini adalah semua mahasiswa psikologi (N=157) yang sedang mengambil skripsi pada semester gasal 2011/2012, berarti berasal dari angkatan 2004–2008. data diperoleh melalui survei dengan angket Pure Procrastination Scale (PPS), EVID 2, dan Pola Asuh Orang Tua (PAQ). Data non-parametrik dianalisis dengan teknik korelasi Spearman menggunakan program SPSS 16.0 for Windows. Hasil menunjukkan tiga temuan, yakni: Pertama, tidak adanya korelasi antara prokrastinasi akademik dan pola asuh orang tua. Kedua, adanya hubungan antara prokrastinasi akademik dan pola asuh otoritatif orang tua. Ketiga, tidak adanya hubungan antara prokrastinasi akademik dan pola asuh permisif orang tua. Terdapat data penunjang dalam penelitian ini, yakni adanya hubungan negatif antara pola asuh orang tua dan kebutuhan berprestasi.